The Use of Youtube Videos to Develop Students’ Writing Skill in Narrative Text - Prihatini, Fajar; Prihatin, Yoga; Sani, Naras (Jurnal Bahasa Inggris, 2018)
The objective of this research is to find out whether there is positive effect of applying Youtube videos on the Grade XI students’ writing skill of Senior High School. The instrument used in this research was writing test about narrative text based on Youtube videos. The test was conducted after the two groups got treatment for 6 meetings. The test is carried out to find out whether students who were taught by using Youtube videos get better writing skill than students who are not taught by using Youtube videos. Data analysis of this research was tested by using t-test in order to find out whether the research hypothesis was accepted or not. Based on the calculation, the t-ratio is 2,998. It was consulted with t-table on the significant level (α) of 5% and the degree of freedom (df) was 38. The t-table obtained was 1,686. It proves that t-ratio is higher than t-table (2,998>1,686), so the hypothesis of the research is accepted. Furthermore, the conclusion of this research is that Youtube videos give positive effect on the writing skill to teach writing to the students who are taught by using Youtube videos. It is suggested for the teacher to apply Youtube videos in the teaching writing. It can be used to solve the students’ difficulties in writing narrative text. Therefore, they can improve students’ writing skill.